2020
DOI: 10.1108/ijlma-02-2019-0038
|View full text |Cite
|
Sign up to set email alerts
|

Blowing the whistle on workplace corruption: the role of ethical leadership

Abstract: Purpose The purpose of this study is to provide a structural model of the role of ethical leadership on intent to whistle blow workplace corruption using the theory of planned behaviors. Design/methodology/approach The study used a mixed method, sequential design. Interviews were conducted in the first phase to identify corrupt practices and validate the salience of the variables in the study. The second phase administered surveys to test the hypotheses of the study. Structural equation modeling (SEM) was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The higher-order leadership theme contained five lowerorder themes, which included ethical management, managerial reactions, communication, leadership style, and dissimilarity between manager and employee. Eleven studies reported a positive relationship between ethical management and whistleblowing intentions (Chiasson et al, 1995;Near et al, 2004;Bhal and Dadhich, 2011;Kaptein, 2011;Alleyne, 2016;Wen and Chen, 2016;Zhang et al, 2016;Cheng et al, 2019;Ugaddan and Park, 2019;Hechanova and Manaois, 2020). If an individual thought that a manager may react negatively to whistleblowing or had reacted negatively in the past, people were less intent on blowing the whistle (Perry et al, 1997;Alleyne et al, 2013;Zhang et al, 2013;Scheetz and Fogarty, 2019).…”
Section: Leadershipmentioning
confidence: 99%
“…The higher-order leadership theme contained five lowerorder themes, which included ethical management, managerial reactions, communication, leadership style, and dissimilarity between manager and employee. Eleven studies reported a positive relationship between ethical management and whistleblowing intentions (Chiasson et al, 1995;Near et al, 2004;Bhal and Dadhich, 2011;Kaptein, 2011;Alleyne, 2016;Wen and Chen, 2016;Zhang et al, 2016;Cheng et al, 2019;Ugaddan and Park, 2019;Hechanova and Manaois, 2020). If an individual thought that a manager may react negatively to whistleblowing or had reacted negatively in the past, people were less intent on blowing the whistle (Perry et al, 1997;Alleyne et al, 2013;Zhang et al, 2013;Scheetz and Fogarty, 2019).…”
Section: Leadershipmentioning
confidence: 99%
“…Arslan [ 80 ] combines three types of exploitation—financial, physical, and psychological—that lead to labor unhappiness in Pakistan’s garment industry. According to Hechanova and Manaois [ 81 ], employee attitudes in the Philippines as well as organizational norms and controls are all influenced by ethical leadership that is subject to job satisfaction. Employee satisfaction with supervision is positively correlated in Malaysia with reward, referent, and expert powers [ 82 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existence of a fraud reporting system, or often referred to as a whistleblowing system, encourages employees and external parties to take an active role in providing information on fraud (Hechanova, M, & Manaois, 2020;Park & Lewis, 2019;Su, 2020). This whistleblowing system can serve as a warning to reveal fraud (Archambeault & Webber, 2015;Chaudhary, Gupta, & Phoolka, 2019;Mbago, Ntayi, & Mutebi, 2018).…”
Section: Introductionmentioning
confidence: 99%